2010
DOI: 10.1111/j.1440-172x.2010.01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐compassion and emotional intelligence in nurses

Abstract: Nurses often provide care for patients and families who are suffering and where emotions are heightened. Compassion is an essential component of the care that nurses provide. Emotions play an important role in the relationship and communication between nurses, patients and families. Self-compassion is the ability to be compassionate to oneself, without this ability nurses might not be prepared to be compassionate to patients. Emotionally intelligent persons perceive themselves as confident, better able to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
147
2
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(175 citation statements)
references
References 24 publications
10
147
2
16
Order By: Relevance
“…Furthermore, in line with our expectations, the results of this study strongly indicated that the self-compassion program lead to an important increase in positive affect levels (Heffernan, Griffin, McNulty & Fitzpatrick, 2010;HollisWalker & Colosimo, 2011;Neff, Rude, & Kirkpatrick, 2007;Neff, 2009), as well as to a decrease in negative affect levels and symptoms of depression, anxiety and stress (Choi, Lee, & Lee, 2014;Leary et al, 2007). We hypothesized that increased levels of positive emotions may act as a mediator in increasing levels of subjective happiness and life satisfaction.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, in line with our expectations, the results of this study strongly indicated that the self-compassion program lead to an important increase in positive affect levels (Heffernan, Griffin, McNulty & Fitzpatrick, 2010;HollisWalker & Colosimo, 2011;Neff, Rude, & Kirkpatrick, 2007;Neff, 2009), as well as to a decrease in negative affect levels and symptoms of depression, anxiety and stress (Choi, Lee, & Lee, 2014;Leary et al, 2007). We hypothesized that increased levels of positive emotions may act as a mediator in increasing levels of subjective happiness and life satisfaction.…”
Section: Discussionsupporting
confidence: 75%
“…In other words, higher selfcompassion levels seem to lead to higher levels of positive mind-states, such as life satisfaction, happiness, connectedness, self-confidence, optimism, curiosity, positive affect and gratitude (Heffernan, Griffin, McNulty, & Fitzpatrick, 2010;Hollis-Walker & Colosimo, 2011;Neff, Rude, & Kirkpatrick, 2007;Neff, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…From a possible range of 210, the mean of the global EI in this study was 155.98. According to Heffernan et al (2010), in a review of studies using the TEIQue-SF scale, no mean scores were indicated and therefore no comparison is possible. The mean of 155.98 is indicative of a higher range of emotional intelligence.…”
Section: Global Emotional Intelligencementioning
confidence: 99%
“…Researchers found relationship between emotional intelligence and self-compassion (Heffernan et al, 2010;Hollis-Walker & Colosimo, 2011). The emotional intelligence has an effect in physical health, and mental, and academic performance (Mayer et al, 2008;Mayer et al, 2002;O´Boyle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%